High-precision position control of hydraulic support pushing system based on quasi-sliding mode - GAO Yuhao; SUN Xing; LI Yang; LIU Wei; LI Jingyan (Gong-kuang zidonghua, 2025)
The control accuracy of the hydraulic support pushing system directly affects the straightness of the fully mechanized mining face. At present, most position control algorithms for front hydraulic support pushing systems suffer from limited state perception dimensions and complex dynamic disturbance coupling, which limits the actual effectiveness of the control algorithms. In particular, nonlinear friction effects and unmodeled dynamic characteristics during the advancing process further aggravate the cumulative effect of system control deviations. To address the above problems, a quasi-sliding mode-based high-precision position control method for hydraulic support pushing systems was proposed. First, a nonlinear model integrating hydraulic cylinder dynamics, flow characteristics, and disturbance coupling was established. A "double-power reaching law and novel saturation function" coordinated framework was proposed to address the contradiction between fast convergence and chattering suppression in traditional sliding mode control（SMC）. Then, a quasi-sliding mode controller (QSMC) based on an extended state observer (ESO) was designed. The controller employed ESO to estimate unmodeled dynamics and external disturbances of the hydraulic support pushing system. A nonlinear feedback saturation function was adopted to accelerate system state convergence and effectively suppress the inherent chattering of sliding mode control. Simulation results showed that, compared with traditional sliding mode control methods, the proposed method shortened the steady-state time in the step response to 1.1 s, representing a reduction of approximately 47.6%, and the steady-state error approached zero. In the sinusoidal response, stable tracking was achieved within 0.2 s, with a peak error of about 0.001 m, representing a reduction of approximately 94.7%, and it exhibited broader bandwidth characteristics. Under square wave input, the proposed method achieved smooth switching and exhibited stronger robustness.